Pengaruh Kinerja Keuangan Dan GCG Terhadap Financial Distress Pada Perusahaan Sektor Energi yang Terdaftar di BEI Tahun 2020-2023 - Pratama, Flower Indah; Marginingsih, Ratnawaty; Yulianti, Wiwit Rohaeni (Journal of Trends Economics and Accounting Research, 2025)
The growth of power generation in Indonesia has seen a 72% increase in capacity over the past decade, reflecting significant improvements in Indonesia's energy sector. In addition, commodity price fluctuations and high investment needs require companies in the energy sector to effectively manage financial risks well through optimal financial performance and good corporate governance implementation. This study aims to determine the effect of financial performance proxied by (ROA and DER) and good corporate governance proxied by (independent commissioners and institutional ownership) on financial distress in energy sector companies listed on the Indonesia Stock Exchange for the period 2020-2023. This study uses quantitative statistical methods with multiple linear regression approaches through the SPSS program. The study findings indicate that financial performance proxied by ROA and DER partially affects financial distress, each with a significance value of 0.000. Conversely, partially, good corporate governance proxied by independent commissioners produced a sig value of 0.358 and institutional ownership proportion with a sig value of 0.589, indicating that both indicators did not affect financial distress in energy sector companies listed on the IDX for the 2020-2023 period. However, simultaneously, financial performance and good corporate governance have an impact on financial distress in energy sector companies listed on the Indonesia Stock Exchange for the 2020-2023 period with a sig value of 0.000 and an adjusted R Square value of 87.9%.